2012
DOI: 10.1002/adfm.201102155
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Transport Properties of Large, Individual NiCo2O4 Nanoplates

Abstract: Understanding the electrical transport properties of individual semiconductor nanostructures is crucial to advancing their practical applications in high‐performance nanodevices. Large‐sized individual nanostructures with smooth surfaces are preferred because they can be easily made into nanodevices using conventional photolithography procedures rather than having to rely on costly and complex electron‐beam lithography techniques. In this study, micrometer‐sized NiCo2O4 nanoplates are successfully prepared fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
219
2
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 314 publications
(237 citation statements)
references
References 37 publications
10
219
2
6
Order By: Relevance
“…24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59It has been reported that thiospinel NiCo 2 S 4 has a much higher conductivity than its oxide counterpart (NiCo 2 O 4 ) and that it is a semiconductor with a direct band gap of 1.2 eV based on UV-Vis measurements. 6 Yet, the reported UV-Vis spectra 6,19 showed a nearly straight line, unlike the UV-Vis spectra of typical semiconductors, 20 implying that no absorption has actually occurred during the measurement. We observe a similar behavior in our material and find it hard to make any definite conclusion from UV-Vis measurements ( Figure S3).…”
Section: Is Nico 2 S 4 Really a Semiconductor?mentioning
confidence: 99%
“…24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59It has been reported that thiospinel NiCo 2 S 4 has a much higher conductivity than its oxide counterpart (NiCo 2 O 4 ) and that it is a semiconductor with a direct band gap of 1.2 eV based on UV-Vis measurements. 6 Yet, the reported UV-Vis spectra 6,19 showed a nearly straight line, unlike the UV-Vis spectra of typical semiconductors, 20 implying that no absorption has actually occurred during the measurement. We observe a similar behavior in our material and find it hard to make any definite conclusion from UV-Vis measurements ( Figure S3).…”
Section: Is Nico 2 S 4 Really a Semiconductor?mentioning
confidence: 99%
“…It has been demonstrated that Ni x Co 3-x O 4 and polycrystalline NiCo 2 O 4 fi lms at 300 °C exhibit an electrical conductivity of 0.1-0.3 S cm −1 and 0.6 S cm −1 , respectively, while that of hexagonal NiCo 2 O 4 nanoplates reaches up to 62 S cm −1 , which are all much higher than the 3.1 × 10 −5 S cm −1 of Co 3 O 4 . [11][12][13][14][15] The high electronic conductivity, which favors fast electron transfer in NiCo 2 O 4 materials, facilitates their application as electrodes. Meanwhile, simultaneous contributions from both redox couples of Co 3+ / Co 2+ and Ni 3+ /Ni 2+ offer richer redox reactions than those of the two corresponding single metallic oxides, resulting in a notable catalytic and electrocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] Formally, it is an inverse spinel with Ni 2+ ions occupying the octahedral site (O h ) and Co 3+ ions distributed over the O h and tetrahedral site (T d ) but the real cation distribution may significantly differ from this, depending on the preparation method. 19 The conduction mechanism is still a subject of discussion and a large variation in the resistivity values is reported in literature.…”
Section: Introductionmentioning
confidence: 99%